Литература прошлого и современность: диалог времен в романе Джона Фаулза «Женщина французского лейтенанта» - Полховская, Е.В.; Терновая, Т.Ю. (Кримський науковий центр НАН України і МОН України, 2006)
Данная статья посвящена изучению произведений английского писателя-
постмодерниста Джона Фаулза. В рамках современного метода интертекстуального анализа особую актуальность приобретает тема выявления литературной преемственности. Новизна темы исследования заключается в изучении
диалогического характера творчества Джона Фаулза. Надана стаття присвячена вивченню творів англійського письменника-
постмодерніста Джона Фаулза. У рамках сучасного методу інтертекстуального
аналізу особливу актуальність набуває тема виявлення літературної спадкоємності. Новизна теми дослідження міститься у вивченні діалогічного характеру творчості Джона Фаулза. The article is devoted to the traditional consideration of John Fowles' novel
"French Lieutenant's Woman". The writer enjoys a justifiably high standing as both a
novelist of outstanding imaginative power and as highly self-conscious 'postmodernist'
author who fully registers the artifice inherent literary traditions in the act of writing.
The author makes the attempt to recreate traditional connections in English literature
by means of cultural and historical dialogue. The article develops the idea of
strong connection of John Fowles' creative works and the literary heritage of the past.